The First Computer-Generated Greek New Testament. - Bunning, Alan (TC: A Journal of Biblical Textual Criticism, 2023)
A plausible Greek New Testament text can be automatically generated by a computer program using statistical analysis and algorithms that weigh the earliest manuscript data in a manner simulating a reasoned-eclecticism approach. This method offers several substantial advantages by providing a consistently weighed text that is openly transparent, without any theological bias, and scientifically reproducible, and the results are very similar to our best modern critical tests. This initial accomplishment could have a number of future implications for the field of textual criticism regarding advances in the use of statistics and algorithms for further refinements in the production of critical texts.